FKIP For Society: Penyuluhan Pendidikan dan Bakti Sosial di Cisarua Kabupaten Bogor - Syamiya, Estu Niana; Swara, Marrieta Moddies; Hubi, Zindan Baynal; Cahyadijaya, Yosean (LP2M INSURI Ponorogo, 2022)
One of the manifestations of humans in socializing is someone who is educated and is able to interact and create a new culture by having global insight. Awareness of the academic community about the importance of interaction with villagers in counseling and social service in the Cisarua area is the goal of this Community Service (PKM) activity. The Cisarua Village is one of the tourist areas in Bogor Regency. The method used in the direct approach, is survey, lecture/counseling, discussion, and evaluation. The activity step begins with students going directly to the field, interviewing villagers, and providing education, technology, and English education. Selina provides social assistance. The activity was carried out in Cisarua village, Bogor Regency, West Java. Through this PkM, participants/citizens who attend can increase motivation in technology education by mastering English, this makes it easier to interact with domestic and foreign tourists in the Industrial 4.0 era